2022
DOI: 10.1523/eneuro.0487-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Mu-Opioid Receptors on Glutamatergic and GABAergic Neurons to Analgesia Induced by Various Stress Intensities

Abstract: The endogenous opioid system plays a crucial role in stress-induced analgesia. Mu-opioid receptors (MORs), one of the major opioid receptors, are expressed widely in subpopulations of cells throughout the CNS. However, the potential roles of MORs expressed in glutamatergic (MOR Glut ) and γ-aminobutyric acidergic (MOR GABA ) neurons in stress-induced analgesia remain unclear. By examining tail-flick latencies to noxious radiant heat of male mice, here we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…S4V–Y ). These CEA neurons are known to be GABAergic [ 6 ]; thus, this result is consistent with previous studies showing that MORs in GABAergic neurons are involved in endogenous opioid analgesia [ 6 , 7 ]. In contrast, we found that the ablation of MOR-expressing neurons in the ACB, which is enriched with GABAergic neurons, did not affect CFA-induced persistent hyperalgesia (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…S4V–Y ). These CEA neurons are known to be GABAergic [ 6 ]; thus, this result is consistent with previous studies showing that MORs in GABAergic neurons are involved in endogenous opioid analgesia [ 6 , 7 ]. In contrast, we found that the ablation of MOR-expressing neurons in the ACB, which is enriched with GABAergic neurons, did not affect CFA-induced persistent hyperalgesia (Fig.…”
Section: Resultssupporting
confidence: 91%
“…An important issue of MOR involvement in endogenous opioid antinociception is whether MORs in the CEA are activated by locally released opioids. Enhanced release of opioids in the brain has been observed in several situations, such as stress-induced analgesia, and the effects could be blocked by naloxone [ 3 , 5 , 7 ]. Consistently, our pharmacological experiments showed that bilateral CEA infusion of naloxone, a competitive opioid antagonist in wild-type mice, blocked endogenous opioid antinociception, indicating the requirement of opioid receptor activation by endogenous opioid peptides during CFA-induced persistent hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that the lack of MORs may affect the behavioral and respiratory responses to the stress associated with intraperitoneal injection. In fact, endogenous MOR circuits are involved in stress (Du et al, 2022), and the absence of MORs may affect the stress response following injection. Overall, our results showed that respiratory rate depression by fentanyl was mediated by MORs in freely behaving mice.…”
Section: Role Of Mors In Opioid-induced Respiratory Rate Depressionmentioning
confidence: 99%
“…The MOR localizes in γ-aminobutyric acid ( GABA ) interneurons in the neocortex and is proposed to disinhibit glutamate-driven outflow to its terminal fields ( Taki et al, 2000 ; Ferezou et al, 2007 ). A subset of cortical glutamate neurons is also reported to express MOR ( Birdsong et al, 2019 ; Zhang et al, 2020 ; Du et al, 2022 ). Opportunistically, the 5-HT 2A R localizes within these key regions ( Figure 1 ) ( Liu et al, 2014 ; Howell and Cunningham, 2015 ; Browne et al, 2019 ; Cunningham et al, 2020 ; Nagai et al, 2020 ).…”
Section: The 5-ht 2a R As a Target For Opioid Use ...mentioning
confidence: 99%